Security for wireless ad hoc networks - Anjum, Farooq (Wiley-Interscience, 2007)
This book addresses the problems and brings solutions to the security issues of ad-hoc networks. Topics included are threat attacks and vulnerabilities, basic cryptography mechanisms, authentication, secure routing, firewalls, security policy management, and future developments.